Pomen gledaliških igric v prvem starostnem obdobju v vrtcu - Šinko, Sabina (Revija za elementarno izobraževanje, 2020)
Importance of Introducing Simple Drama Games to Kindergarten Children of the First Age Group. This article discusses the importance of introducing simple drama games to kindergarten children of the first age group. Based on the knowledge and experience of experts from countries where such games are played and used in kindergartens on a daily basis, we can clearly talk about a positive impact they have on child’s cognitive, emotional, social, and motor development. As examples of good practice, we showcase the findings of theses by students of Preschool Education at the Faculty of Education in Maribor.
Keywords: drama games; drama in education; kindergarten